The Durability and Treatability of Populus deltoides Marsh - Dobriyal, P. B.; Chauhan, K. S.; Dev, Indra (Indian Forester, 2001)
Treatability of Poplar wood on the basis of penetration indices has shown that it is a easily treatable wood. Regarding the natural durability, it is non durable species at ground contact and require preservative treatment to get adequate service life for better end utilisation.